PENGARUH PEMBERIAN NAA DAN KINETIN TERHADAP PERTUMBUHAN EKSPLAN BUAH NAGA (Hylocereus costaricensis) MELALUI TEKNIK KULTUR JARINGAN SECARA IN VITRO - Imam Mahadi; Sri Wulandari; Delfi Trisnawati (Program Studi Pendidikan Biologi, 2013)
This research aimed to determine the effect of NAA and Kinetin on the growth of explants dragon fruit (Hylocereus costaricensis). This research was conducted at the Laboratory of Biology Education University of Riau and Laboratory Biotechnology of Riau Islamic University from May to August 2012, using a completely randomized design of 3 x 3 factorial with four replications. The first factor (N) is the NAA consists of 3 level: 0 ppm, 0.2 ppm and 0.4 ppm. The second factor (K) is the Kinetin consist of 3 level: 0 ppm, 3 ppm and 4 ppm. Parameters measured were percentage grows, the amount of buds and amount of roots. The data were analyzed using ANAVA and tested further by DMRT at 5% level. The results of this research showed of NAA and Kinetin significantly affect the growth of explants Dragon Fruit. The percentage of explants grown 100% all treatments, except treatment N0 K4, N0,2 K0 and N0,2 K3. Highest amount of buds in treatment N0,4 K3 is 2.25 buds and the amount of roots the best treatment of N0,4 K4 is 5.25 roots. Based on the results of the research treatment N0,4 K4 is the best treatment.Keywords: Kinetin, NAA, Tissue culture.